Ecosystem services of boreal forests – Carbon budget mapping at high resolution. (1st October 2016) - Akujärvi, Anu; Lehtonen, Aleksi; Liski, Jari
Abstract: The carbon (C) cycle of forests produces ecosystem services (ES) such as climate regulation and timber production. Mapping these ES using simple land cover -based proxies might add remarkable inaccuracy to the estimates. A framework to map the current status of the C budget of boreal forested landscapes was developed. The C stocks of biomass and soil and the annual change in these stocks were quantified in a 20 × 20 m resolution at the regional level on mineral soils in southern Finland. The fine-scale variation of the estimates was analyzed geo-statistically. The reliability of the estimates was evaluated by comparing them to measurements from the national multi-source forest inventory. The C stocks of forests increased slightly from the south coast to inland whereas the changes in these stocks were more uniform. The spatial patches of C stocks were larger than those of C stock changes. The patch size of the C stocks reflected the spatial variation in the environmental conditions, and that of the C stock changes the typical area of forest management compartments. The simulated estimates agreed well with the measurements indicating a good mapping framework performance. The mapping framework is the basis for evaluating the effects of forest management alternatives on C budget at high resolution across large spatial scales. It will be coupled with the assessment of other ES and biodiversity to study their relationships. The framework integrated a wide suite of simulation models and extensive inventory data. It provided reliable estimates of the human influence on C cycle in forested landscapes. Highlights: The forest carbon (C) budget was mapped at a high resolution across a large region. Biomass and soil C stocks had a regional trend unlike the changes in these C stocks. The spatial autocorrelation of C stocks was larger than that of C stock changes. The framework produced reliable estimates of C budget in boreal forested landscapes. The framework will be applied to evaluate forest management effects on C budget.